Gastrointestinal Neuroendocrine Tumors: Clinical and Pathological Correlates - Datta, Sanjit; Sinha, Annika; Kapoor, Baljendra (Digestive Disease Interventions, 2019)
Gastrointestinal neuroendocrine tumors (GI-NETs), previously classified as carcinoid tumors, are rare cancers that arise from cells of the diffuse endocrine system of the gastrointestinal tract. These tumors most commonly arise from the bronchus, jejunoileum, or colon/rectum. They produce peptide products that can lead to identifiable clinical syndromes such as carcinoid syndrome, which is classically associated with diarrhea, flushing, and heart disease. The latest classifications of GI-NETs include pancreatic NETs, which can produce a wide range of pancreatic hormones leading to syndromes such as Zollinger–Ellison's syndrome. The prognosis for patients with GI-NETs varies widely depending on the size, location, and presence of metastatic disease, with 5-year survival rates ranging from 0 to 15% for poorly differentiated NETs and 10-year survival rates of up to 100% for patients with insulinomas smaller than 2 cm. A wide range of treatment modalities is commonly used to treat GI-NETs, including surgical and endoscopic resection, locoregional therapies, cytotoxic chemotherapy, and somatostatin receptor targeted therapy. The goal of this review is to detail the classification, epidemiology, clinical syndromes, diagnosis, and staging of these tumors and to provide an overview of management strategies.
Keywords: gastrointestinal neuroendocrine tumors; carcinoid; carcinoid syndrome; pancreatic neuroendocrine tumors; serotonin